2016
DOI: 10.1111/ijfs.13214
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ubiquitin‐proteasome pathway on proteolytic activity in postmortem proteolysis and tenderisation of sheep skeletal muscle

Abstract: Summary The objective of this study was to investigate the effects of ubiquitin‐proteasome pathway on meat tenderisation. The sheep muscle longissimus lumborum was injected with or without PYR‐41 (inhibitor of ubiquitination) or MG‐132 (inhibitor of proteasome). Muscle samples were collected at 6, 15, 24 and 48 h after injection. Myofibrillar protein degradation, muscle ultrastructure and sarcomere length were determined. Results showed that inhibition of proteasome or ubiquitination affected sarcomere length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…BIRC6 is part of the ubiquitin-mediated proteolysis pathway and was positively associated with M17. By impairing proteolysis, the up-regulation of BIRC6 likely increases shear force ( Liu et al, 2016 ). Genes from the E3 ubiquitin-protein ligase family ( HERC1, HERC2, HUWE1, ITCH , and UBR5 ) were also identified in agreement with a recent report that found ubiquitination and apoptosis to be potential regulators of meat tenderness in Nelore cattle ( Gonçalves et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…BIRC6 is part of the ubiquitin-mediated proteolysis pathway and was positively associated with M17. By impairing proteolysis, the up-regulation of BIRC6 likely increases shear force ( Liu et al, 2016 ). Genes from the E3 ubiquitin-protein ligase family ( HERC1, HERC2, HUWE1, ITCH , and UBR5 ) were also identified in agreement with a recent report that found ubiquitination and apoptosis to be potential regulators of meat tenderness in Nelore cattle ( Gonçalves et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TEM examination of muscle structure was conducted as described by Liu et al . () with some modification. Muscle (4 × 2 × 2 mm) was submitted to double fixation, (2% glutaraldehyde, pH 7.4; 1.0% osmium tetroxide), dehydrated through a graded ethanol (30%, 50%, 60%, 70%, 80%, 90%, 100%), replaced three times with anhydrous acetone and then embedded in an Epon–Araldite mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that muscle atrophy occurs due to increased proteolysis due to the activation of the ubiquitin-proteasome pathway (Jagoe and Goldberg, 2001;Bodine and Baehr, 2014;Liu et al, 2016). In particular, muscle atrophy F-box (MAFbx)/atrogin-1 and muscle RING finger-1 (MuRF-1), which are muscle-specific ubiquitin ligases, are expressed early in the muscle atrophy process and are directly involved in muscle protein degradation (Bodine and Baehr, 2014;Liu et al, 2016).…”
Section: Inhibitory Activity Of Deer Antler Extracts On Muscle Atrophy Factors In Aicar-induced Muscle Atrophied C2c12 Cellsmentioning
confidence: 99%